2020
DOI: 10.1002/jsfa.10331
|View full text |Cite
|
Sign up to set email alerts
|

Myzus persicae (Hemiptera: Aphididae) infestation increases the risk of bacterial contamination and alters nutritional content in storage Chinese cabbage

Abstract: BACKGROUND Aphids are common insect pests that feed on and excrete feces/honeydew on storage vegetables, especially in the temperate region of the northern hemisphere. The honeydew of aphids is an excellent growth medium for microorganisms. To explore the effects of aphid infestation on the risk of microbial contamination and food safety: (i) the bacterial diversity and community in aphid honeydew were investigated; (ii) the nutritional components of the cabbage were analyzed; and (iii) safety was evaluated. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The honeydew is vulnerable to be contaminated by microorganisms especially in the hot and humid regions [ 7 , 11 ]. It has been reported that the honeydew of scale insects and aphids is a source of nourishment to some microorganisms [ 12 ]. For E. pela , the honeydew they secrete is a good culture medium for Cladosporium genus fungi [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The honeydew is vulnerable to be contaminated by microorganisms especially in the hot and humid regions [ 7 , 11 ]. It has been reported that the honeydew of scale insects and aphids is a source of nourishment to some microorganisms [ 12 ]. For E. pela , the honeydew they secrete is a good culture medium for Cladosporium genus fungi [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This aphid is known to extract nutrients from the phloem and xylem of more than 400 plant species in over 50 families (Smith, 1926;van Emden et al, 1969, van Emden andHarrington, 2017;Weber, 1986;Spiller et al, 1990;Bernays and Chapman, 1994;Gupta, 2001;Chen et al, 2020), including both row crops and ornamentals grown in greenhouses. M. persicae reduces crop yields by causing systemic perturbations in nutrient allocation, leaf discoloration and necrosis, and leaf and/or fruit deformation (Zhan et al, 2020). Furthermore, M. persicae is one of the most effective vectors for plant viruses (Ng and Perry, 2004;Ng and Falk, 2006) and can transmit a large number of economically important viruses in a persistent, semi-persistent, or non-persistent manner (Carmo-Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%